Cães intoxicados com folhas frescas de Nerium oleander: Achados clínicos e eletrocardiográficos - Camplesi, Annelise Carla [UNESP]; Bellodi, Carolina [UNESP]; Socha, José Javier Mesa [UNESP]; Hatayde, Mário Roberto [UNESP]; Sobreira, Márcia Ferreira da Rosa [UNESP]; Araujo, Gustavo Henrique Marques; Araujo, Carla Fredrichsen Moya (FapUNIFESP (SciELO), 2017)
Nerium oleander is distributed worldwide, mainly in tropical and subtropical regions. These shrubs are frequently used as ornamental plants. However, they contain more than 30 cardiac glycosides that can cause serious toxic effects in dogs. The objective of this study was to report the clinical and electrocardiographic alterations in dogs experimentally poisoned with N. oleander. Ten adult, healthy, mixed-breed dogs weighing 10- 25kg and aged 3-6 years were selected for the study. We orally administered 0.25g kg-1 of fresh ground leaves of N. oleander to the dogs. No dog died after the ingestion, but all exhibited signs of poisoning such as vomiting, sialorrhea, nausea, apathy, conjunctiva congestion, dehydration, abdominal pain, tremors, diarrhea, loss of appetite, and tenesmus. Electrocardiogram revealed occurrence of several types of arrhythmias: sinus bradycardia, second-degree atrioventricular block, paroxysmal ventricular tachycardia, and ventricular premature complexes. Systolic blood pressure, as well as heart rate, decreased in the first 24 hours. The present study concluded that a single dose of 0.25g kg-1 of N. oleander green leaves is sufficient to cause a moderate intoxication in dogs, with nonspecific clinical changes mainly related to the digestive system and heart rate, thus demonstrating the importance of this type of intoxication in the list of differential diagnoses of small animals routine.
Poisoned with Nerium oleander fresh leaves: Clinical and electrocardiographic findings
Keywords: Arrhythmia; Blood pressure; Canine; Cardiac glycosides; Electrocardiography